Minimum quality standards and non-compliance - Laura Birg; Jan S. Voßwinkel (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
This paper studies the effect of non-compliance with a minimum quality standard on prices, quality, and welfare in a vertical differentiation model. Non-compliance with a minimum quality standard by a low-quality firm reduces quality levels of both firms, increases the price for the high-quality product, decreases the price for the low-quality product, and shifts demand from the low-quality to the high-quality firm. Under non-compliance, an increase in the standard increases the quality difference, increases the price difference, and shifts demand from the high-quality to the low-quality firm. Stricter government enforcement decreases the quality level of the low-quality firm, increases the price of the high-quality product and shifts demand from the low-quality firm to the high-quality firm. Non-compliance of the low quality firm increases profits for both firms, reduces consumer surplus and increases or decreases welfare depending on the market size, the effect of quality levels of the externality, the detection probability, and the minimum quality level.
Keywords: K42; L13; L50; 330; minimum quality standard; non-compliance; enforcement